Rh Blood Group System: Clinical Significance, Laboratory Testing, and Transfusion Safety (The Review of Diabetic Studies, 2024)
Background: The Rh blood group system is one of the most clinically significant antigen systems in transfusion medicine and obstetric care. Its strong immunogenicity makes Rh incompatibility a major cause of alloimmunization, hemolytic transfusion reactions, and hemolytic disease of the fetus and newborn (HDFN).Aim: To review the clinical significance, laboratory testing methods, and transfusion safety considerations related to the Rh blood group system.Methods: This review synthesizes historical, genetic, and immunohematologic data on Rh antigen structure, variant phenotypes, and diagnostic testing. It evaluates serologic and molecular approaches for Rh typing, antiglobulin testing, and quality control measures essential for accurate interpretation.Results: The Rh system comprises over 50 antigens, with D antigen being the most immunogenic. Variant phenotypes such as weak D, partial D, and Rhnull complicate serologic interpretation and increase alloimmunization risk. Diagnostic strategies include direct and indirect antiglobulin tests (DAT/IAT), tube and gel methods, and molecular genotyping for ambiguous cases. Preventive measures, such as Rh immune globulin prophylaxis and strict transfusion compatibility protocols, have significantly reduced HDFN incidence. Quality assurance practices, including reagent verification and proficiency testing, remain critical for patient safety.Conclusion: Accurate Rh typing and antibody screening are indispensable for safe transfusion and obstetric management. Integration of advanced serologic and molecular techniques with robust quality systems ensures reliable results and minimizes immunologic risk.